2021
DOI: 10.1113/jp281056
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of longitudinal dentate gyrus axons associated with seizure

Abstract: Key points Axon collaterals of DG granule neurons project towards neighbouring DG granule cell layer Longitudinal axons in the DG‐DG circuit possess denser synapses than transverse axons in the DG‐CA3 circuit The size of varicosities of the longitudinal axons, but not transverse ones, is regulated by seizures as measured behaviourally Varicosity size of DG‐DG axons can be a symptomatic marker of DG‐related brain diseases Abstract The hippocampus network has captured the attention of neuroscientists as a mode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 43 publications
(106 reference statements)
0
11
0
Order By: Relevance
“…The observation that NIHL did not alters long-term synaptic plasticity via transverse mossy fibers led us to consider another orientation of DG signal propagation, i.e., the longitudinal DG network along the dorsoventral axis perpendicular to the transverse projection. Based on the previous studies that suggested the existence of a longitudinal connection within the DG network ( Lømo, 2009 ; Claiborne et al., 1986 ; Scharfman and Pierce, 2012 ; Jonas and Lisman, 2014 ; Choi et al., 2021 ), we examined the influence of NIHL on this network. We prepared longitudinal hippocampal slices by cutting the hippocampus along the dorsoventral axis to preserve longitudinal axons ( Figure 3 A) ( Tetteh et al., 2019 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The observation that NIHL did not alters long-term synaptic plasticity via transverse mossy fibers led us to consider another orientation of DG signal propagation, i.e., the longitudinal DG network along the dorsoventral axis perpendicular to the transverse projection. Based on the previous studies that suggested the existence of a longitudinal connection within the DG network ( Lømo, 2009 ; Claiborne et al., 1986 ; Scharfman and Pierce, 2012 ; Jonas and Lisman, 2014 ; Choi et al., 2021 ), we examined the influence of NIHL on this network. We prepared longitudinal hippocampal slices by cutting the hippocampus along the dorsoventral axis to preserve longitudinal axons ( Figure 3 A) ( Tetteh et al., 2019 ).…”
Section: Resultsmentioning
confidence: 99%
“…Neurons in the molecular and granule cell layers receive inputs from the EC and dentate hilus and then send signals to the dentate hilus and CA3 and CA2 regions, respectively ( Kohara et al., 2014 ; Blaabjerg and Zimmer, 2007 ; Swanson et al., 1978 ). In our previous study, we found that primary axons from the DG project transversely (in-lamellar) to the hilus and/or CA3 and bifurcate longitudinally (trans-lamellar) towards the molecular layer, targeting adjacent DGGCs ( Choi et al., 2021 ). This creates diverse DG axonal projection patterns that contain granule and mossy cells ( Lømo, 2009 ; Claiborne et al., 1986 ; Scharfman and Pierce, 2012 ; Jonas and Lisman, 2014 ; Choi et al., 2021 ), as further evidenced by the longitudinal spread of electrical signals along the dorsoventral axis of the hippocampus ( Pare and Llinas, 1994 ; Lømo, 2009 ).…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…The colors indicate representative neurons and their projections: red, DG; blue, CA3; black, CA2; green, CA1; orange, EC. Adapted from previous studies (Andersen et al, 1969(Andersen et al, , 1971Bliss & Lomo, 1973;Choi et al, 2021;Pak et al, 2022;Sloviter & Lomo, 2012;Steffenach et al, 2002;Strange et al, 2014;Sun et al, 2018;Witter et al, 1989;Yang et al, 2014). CA3, cornu ammonis 3; DG, dentate gyrus; EC, entorhinal cortex layer.…”
Section: Interlamellar Connection and Signal Transfer In The Dgmentioning
confidence: 99%
“…direct and bidirectional longitudinal axons between granule cells in the DG (Choi et al, 2021;Pak et al, 2022). The primary axon of a DG granule cell heading to the CA3 region bifurcates to the longitudinal direction.…”
Section: T a B L E 1 Key Studies Of Interlamellar Connections In The ...mentioning
confidence: 99%